Hydrophilic Crosslinked TEMPO‐Methacrylate Copolymers – a Straight Forward Approach towards Aqueous Semi‐Organic Batteries. Issue 18 (27th July 2022) - Elbinger, Lada; Schröter, Erik; Friebe, Christian; Hager, Martin D.; Schubert, Ulrich S.
Abstract: Crosslinked hydrophilic poly(2, 2, 6, 6‐tetramethylpiperidinyl‐ N ‐oxyl‐co‐[2‐(methacryloyloxy)‐ethyl]trimethyl ammonium chloride) [poly(TEMPO‐ co ‐METAC)] polymers with different monomer ratios are synthesized and characterized regarding a utilization as electrode material in organic batteries. These polymers can be synthesized rapidly utilizing commercial starting materials and reveal an increased hydrophilicity compared to the state‐of‐the‐art poly(2, 2, 6, 6‐tetramethylpiperidinyl‐ N ‐oxyl‐4‐methacrylate) (PTMA). By increasing the hydrophilicity of the polymer, a preparation of cathode composites is enabled, which can be used for aqueous semi‐organic batteries. Detailed battery testing confirms that the additional METAC groups do not impair the battery behavior while enabling straight‐forward zinc‐TEMPO batteries. Abstract : Organic cathode in aqueous electrolyte : A crosslinked hydrophilic 2, 2, 6, 6‐tetramethylpiperidine‐ N ‐oxyl radical (TEMPO) bearing polymer was synthesized, which enables aqueous battery chemistries that have not been compatible with poly(TEMPO‐methacrylate) derived structures before. Extensive battery testing was performed, to reveal the battery chemistry of the polymer containing composite electrodes in an aqueous semi‐organic zinc coin‐cell setup.